ECONOMIC DIVERSIFICATION IN SCO MEMBER STATES: OPPORTUNITIES AND CHALLENGES - Adnan Saghir; Muhammad Sohrab Saleem; Dr. Muhammad Fahim Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
Diversification is a critical factor that contributes to the growth and sustainability of economies, especially the member countries of the SCO. The research focuses on the opportunities and challenges of economic diversification in the member countries of the SCO. The variables used for the analysis include dependence on the traditional sectors, the prospects of the new sectors, and the influence of the global economy. Some of the major factors that have been considered as opportunities include energy markets, infrastructure development, technology collaboration, regional liberalization, and FDI inflow. On the other hand, the challenges include internal economic reliance, weak institutional frameworks, underdeveloped technology, visa/bureaucratic impediments, and geopolitics. This paper seeks to present an overview of the current economic status, as well as policies of the SCO member states to analyze and understand the factors that may help the countries to diversify their economies for sustainable growth and stability.